TO STUDY THE EFFECT OF POSITIONAL STRETCH ON MOBILITY ASSESSED BY TIME UP AND GO TEST AMONG POST-STROKE PATIENTS - K Patel, *Jagruti; Patel, Nilima (International Journal of Ayurveda and Pharma Research, 2016)
Background & Objective: Stroke is a disease caused by the disruption of blood vessels in the brain, such as ischemic and hemorrhagic. It is the second most common cause of death and disability worldwide. The Indian Council of Medical Research estimates that among the non-communicable disease, stroke contributes for 41% of deaths and 72% of disability adjusted life years.Mobility as it is a critical part of maintaining independence and an essential attribute of quality of life. Prevention of abnormal muscle shortening is an important component of motor relearning programme of Carr and Shepherd. If this aspect is incorporated early in the rehabilitation programme, then the functional recovery in these patients will be better.Aim: The present study aimed to find out the effect of positional stretch on mobility assessed by Time up and Go Test among Post-stroke patients.Methodology: Sample size was 30.The assessment was focus on the Mobility using Time up and go test and degree of soft-tissue tightness of the four muscles include Iliopsoas, Rectus Femoris, Hamstrings and Gastrosoleus of both the side of body Pre- and Post- intervention.Conclusion: This study shows that Positional soft tissue stretching along with conventional physiotherapy based on Motor Relearning Programme has significant improvement on Mobility in Post Stroke Patients and has significant reduction and correction of the tightness of all four muscles of both Affected and Non-affected side.